PERANCANGAN APARTEMEN SOHO DI SAAT DAN SETELAH PANDEMI COVID 19 - Serine Elisputri; Mieke Choandi (Jurusan Arsitektur dan Perencanaan, 2021)
The rapid spread of Covid-19 in Indonesia has prompted the government to issue policies for PSBB and work from home (WFH). For employees who have far access to their homes and offices, WFH is ideal for maintaining productivity because there is a significant reduction in transportation costs and time. WFH also has obstacles, such as the community's mindset that the house is a place to rest and the office is a place to work, causing mental conflict and decreasing employee productivity. The suggestion to work from home will have a big impact on how we work during and after the pandemic, because WFH teaches that we can do tasks remotely. This problem has prompted the building to be designed to accommodate the needs of the community caused by changes in human life during the pandemic that provides a comfortable home and workplace for the needs of residents after the COVID-19 pandemic. Small Office Home Office (SOHO) concept is a concept that places office activities in an integrated manner. Offices tend to be open to the public are applied to residential spaces that are more private but separate, so that family privacy is still maintained. The target of residents are millennials who work as independent entrepreneurs, MSME entrepreneurs, office workers, freelancers, and online sellers. The method used in this design is in the form of hybrid working which is thinking about the room occupants who work and live simultaneously with the use of current technology. the concepts used are biophilic architecture and green building, which aim to save energy through air, water, and sunlight, such as; the use of voids and split systems on floors with glass roofs in residential corridor areas. Use of a green balcony, open wide windows. On the other hand, increasing green open space as communal space and absorption of water into the soil. The building also uses rain water harvesting and photovoltaic systems to provide energy for the building.Keywords: biophilic architecture; ; green building; residence; work space; work from home AbstrakPenyebaran yang cepat dari Covid-19 di Indonesia membuat pemerintah mengeluarkan kebijakan untuk PSBB dan work from home (WFH). Bagi pegawai yang akses tempat tinggal dan kantornya jauh, WFH sangat ideal untuk menjaga produktivitas karena dengan WFH terdapat pengurangan biaya dan waktu transportasi yang cukup signifikan. Tentunya WFH juga terdapat kendala seperti adanya pola pikir masyarakat bahwa rumah tinggal merupakan tempat istirahat dan kantor merupakan tempat bekerja sehingga menimbulkan konflik dan menurunnya produktifitas pegawai. Anjuran untuk work from home akan berpengaruh besar pada cara kerja saat dan setelah pandemi, karena WFH mengajarkan bahwa kita bisa melakukan tugas secara jarak jauh. Permasalahan ini mendorong bangunan dirancang untuk mewadahi kebutuhan masyarakat yang disebabkan perubahan kehidupan manusia saat pandemi yang menyediakan sebuah rumah tinggal dan tempat kerja yang nyaman bagi kebutuhan penghuni setelah terjadinya pandemi covid 19. Konsep Small Office Home Office (SOHO) merupakan konsep yang menempatkan kegiatan kantor secara fisik pada ruang hunian, Kantor yang sifatnya sosial dan cenderung terbuka untuk publik diterapkan pada ruang hunian yang lebih bersifat privat tetapi terpisah sehingga privasi keluarga masih terjaga. Sasaran penghuni merupakan kaum milenial yang bekerja sebagai pengusaha mandiri, pengusaha UMKM , pekerja kantor, freelancer, dan online seller. Metode yang digunakan dalam rancangan ini berupa hybrid working yaitu, memikirkan ruangan penghuni yang bekerja dan berhuni secara bersamaan dengan pemakaian teknologi saat ini. konsep yang digunakan berupa arsitektur biofilik dan green building yaitu bertujuan untuk menghemat energi melalui udara, air, dan cahaya matahari, seperti; penggunaan void dan split system pada lantai dengan atap kaca di area koridor hunian. Penggunaan green balcony, membuka jendela yang lebar. Disisi lain, memperbanyak ruang terbuka hijau sebagai ruang komunal dan penyerapan air kedalam tanah. Bangunan juga menggunakan rain water harvesting dan photovoltaic system untuk menyediakan energi bagi bangunan.